Implication Abu Dhabi Document: to build religious moderation with brotherhood-sisterhood and friendship in Indonesia - Edison R. L. Tinambunan; I. Ketut Gegel; Peter Bruno Sarbini; Gus Zain Baik (Cogent Arts & Humanities)
Religious moderation is a joint religious movement in Indonesia initiated by the Ministry of Religious Affairs to overcome extremism, fundamentalism, and radicalism. The Abu Dhabi Document issued by Pope Francis and Grand Imam Ahmad Al-Tayyeb provides practical strategies for religious moderation. This research uses a qualitative methodology with an analytical approach to the Abu Dhabi Document to explore the dimensions of religious moderation that can be applied amid the Indonesian plurality. The findings are that brotherhood-sisterhood and friendship, which are the character of humanity, are used for religious moderation. This research aims to instil brotherhood-sisterhood and friendship as a step toward realising religious moderation amid religious diversity in Indonesian society. A suggestion to support this paper is further research on the Abu Dhabi Document from the aspect of interfaith dialogue for a more solid manifestation of religious moderation in Indonesia.